Lapidary Art of the Altai and the Urals of the Late 18th — 19th Centuries: The Russian Cultural Phenomenon and European Influence - Borovkova, Natalia V. (Izvestiâ Uralʹskogo federalʹnogo universiteta. Seriâ 2, Gumanitarnye nauki, 2021)
The study of Russian stone-cutting art remains an important and urgent task of contemporary Russian art history. It is necessary to take a fresh look at this direction of Russian decorative art and find out whether Russian stone-cutting art is an internal phenomenon, or it is based on European borrowing. This article refers to works of stone-cutting enterprises of the Urals and the Altai, i. e. Yekaterinburg and Loktevsk Manufactories, which worked exclusively at the order of the Cabinet. In the late eighteenth century, there was a system for ordering stone products in Russia. To do this, they formed sets of “samples” of natural ornamental stone from Russian deposits and compiled albums of product projects. When sending an order to the factory, they attached a sketch and indicated the number of the stone which the product was to be made of. A complex analysis of Russian stone-cutting art testifies to the fact that it followed European fashion, traditions, and technology. European specialists were invited to Russia in order to organise stone-cutting production. Also, travellers brought elegant artworks made of decorative stone by European masters. By the late eighteenth century, stone-cutting production had come a much longer way in Western Europe than in Russia. The production of works of art made of stone was carried out in Italy, France, England, Sweden, and other European countries. Russian commissioners wanted to obtain similar items, and the masters imitated and reproduced European originals. When comparing designs of decorative vases, one can see an undoubted influence of European analogues. However, if there is an obvious similarity to their decorative design, Russian masters are characterised by the ability to reveal the unique aesthetic properties of the material. At the first stage, the influence of European masters was not to be argued, but later on, Russian stone-cutting art began to acquire its own unique features, although it developed along the lines of the dominating pan-European stylistic trends.